Evaluation of the Implementation of the Micro Teaching Program for Students of the Physical Education Health and Recreation Study Program FKIP Primagraha University - Gunardi, Ari; Anriani, Nurul; Ariestika, Elsa (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2023)
This research aims to determine whether the implementation of the micro teaching program for the 2022–2023 academic year is effective for students of the Physical Education Health and Recreation Study Program, Faculty of Teacher Training and Education, Primagraha University. Study descriptive done with use design study studies survey. Research sample this using 80 students with taking sample use purposive sampling. Instrument study this use questionnaire scale likert. Based on results study 67.5 % of students answered questionnaire about level preparation micro teaching activities are categorized has do it. Study This supported by survey data about aspects not quite enough answer lecturer mentor in implementation of micro teaching, in particular classification of 52.5% of them classified moderate / fair in matter guidance student. Based on results survey, found 50.84% of students Enough capable carry out micro teaching practice in the microteaching laboratory. Based on the percentage results, it is stated that in terms of implementing micro teaching, it has not achieved success because it has not achieved 100% of the overall assessment aspects which really support the implementation of micro teaching practice.